Simulation-based training for embryo transfer for clinicians with differing levels of expertise: an application of the American Society for Reproductive Medicine Embryo Transfer Simulator - Katherine M. Baker, M.D; Angela Q. Leung, M.D; Jaimin S. Shah, M.D; Ann Korkidakis, M.D; Denny Sakkas, Ph.D; Alan Penzias, M.D; Thomas L. Toth, M.D (Elsevier, 2023)
Objective: To compare the learning curve of clinicians with different levels of embryo transfer (ET) experience using the American Society for Reproductive Medicine (ASRM) Embryo Transfer Simulator. Design: Prospective cohort study. Setting: Single large university-affiliated in vitro fertilization center. Patient(s): Participants with 3 levels of expertise with ET were recruited: "group 1" (Reproductive Endocrinology and Infertility attendings), "group 2" (Reproductive Endocrinology and Infertility nurses, advance practice providers, or medical assistants), and "group 3" (Obstetrics and Gynecology resident physicians). Intervention(s): All participants completed ET simulation training using uterine cases A, B, and C (easiest to most difficult) of the ASRM ET Simulator. Participants completed each case 5 times for a total of 15 repetitions. Main Outcome Measure(s): The primary outcome was ET simulation scores analyzed at each attempt for each uterine case, with a maximum score of 155. Secondary outcomes included self-assessed comfort levels before and after the completion of the simulation and total duration of ET. Comfort was assessed using a 5-point Likert scale. Result(s): Twenty-seven participants with 3 different levels of expertise with ET were recruited from December 2020 to February 2021. For cases A and B, median total scores were not significantly different between groups 1 and 3 at first or last attempts. Group 2 did not perform as well as group 3 at the beginning of case A or group 1 at the end of case B. All groups demonstrated a decrease in total time from the first attempt to the last attempt for both cases. For case C, the "difficult" uterus, groups 2 and 3 exhibited the greatest improvement in total median score: from 0 to 75 from the first to last attempt. Group 1 scored equally well from first through last attempts. Although no one from group 2 or 3 achieved a passing score with the first attempt (80% of the max score), approximately 30% had passing scores at the last attempt. Groups 1 and 3 showed a significant decrease in total time across attempts for case C. Following simulation, 100% of groups 2 and 3 reported perceived improvement in their skills. Group 3 showed significant improvement in comfort scores with Likert scores of 1.71 ± 0.76 and 1.0 ± 0.0 for the "Easy" and "Difficult" cases, respectively, before simulation and 4.57 ± 0.53 and 2.4 ± 1.1 after simulation. Conclusion(s): The ASRM ET Simulator was effective in improving both technical skill and comfort level, particularly for those with little to no ET experience and was most marked when training on a difficult clinical case.